2003
DOI: 10.1056/nejmoa022048
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Cerebrovascular Events in Patients Treated for Human Immunodeficiency Virus Infection

Abstract: Use of newer therapies for HIV was associated with a large benefit in terms of mortality that was not diminished by any increase in the rate of cardiovascular or cerebrovascular events or related mortality. Fear of accelerated vascular disease need not compromise antiretroviral therapy over the short term. However, prolonged survival among HIV infected patients means that longer-term observation and analysis are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
337
4
18

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(369 citation statements)
references
References 21 publications
10
337
4
18
Order By: Relevance
“…Some of this risk was associated with dyslipidemia [83]. Other cohorts have not shown an increased risk for cardiovascular disease for patients on any type of ARV [84]. The reason for this discrepancy is not clear but will hopefully be clarified as more data are available.…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…Some of this risk was associated with dyslipidemia [83]. Other cohorts have not shown an increased risk for cardiovascular disease for patients on any type of ARV [84]. The reason for this discrepancy is not clear but will hopefully be clarified as more data are available.…”
Section: Protease Inhibitorsmentioning
confidence: 99%
“…Several other studies have also reported an association between PI and CVD, 24,51,74,75 although others have not. 76 Data on the association between NRTI and NNRTI use and CVD are more limited. In the D:A:D study, NNRTI was not associated with increased MI risk, 16 and data from the Veterans Affair also were unable to demonstrate an association.…”
Section: Antiretroviral Treatment and Cvdmentioning
confidence: 99%
“…hypertension, diabetes or increased plasma homocysteine levels) might be at raised risk of developing coronary artery disease because of accelerated atherosclerosis. Conflicting data exist, however, on the relationship between HAART and incidence of acute coronary syndromes, such as unstable angina or myocardial infarction, among HIV-infected patients receiving PI-containing HAART [85][86][87][88][89] . Differences in the study design, selection of patients and statistical analyses might explain this disparity.…”
Section: Haart-associated Coronary Artery Diseasementioning
confidence: 99%